A decade of ejecta dust formation in the Type IIn SN 2005ip. Issue 4 (8th March 2019) - Bevan, A; Wesson, R; Barlow, M J; De Looze, I; Andrews, J E; Clayton, G C; Krafton, K; Matsuura, M; Milisavljevic, D
ABSTRACT: In order to understand the contribution of core-collapse supernovae to the dust budget of the early Universe, it is important to understand not only the mass of dust that can form in core-collapse supernovae but also the location and rate of dust formation. SN 2005ip is of particular interest since dust has been inferred to have formed in both the ejecta and the post-shock region behind the radiative reverse shock. We have collated eight optical archival spectra that span the lifetime of SN 2005ip and we additionally present a new X-shooter optical–near-IR spectrum of SN 2005ip at 4075 d post-discovery. Using the Monte Carlo line transfer code damocles, we have modelled the blueshifted broad and intermediate-width H α, H β, and He i lines from 48 to 4075 d post-discovery using an ejecta dust model. We find that dust in the ejecta can account for the asymmetries observed in the broad and intermediate-width H α, H β, and He i line profiles at all epochs and that it is not necessary to invoke post-shock dust formation to explain the blueshifting observed in the intermediate-width post-shock lines. Using a Bayesian approach, we have determined the evolution of the ejecta dust mass in SN 2005ip over 10 yr presuming an ejecta dust model, with an increasing dust mass from ∼10 −8 M⊙ at 48 d to a current dust mass of ∼0.1 M⊙ .